Exploring thermal comfort in the context of historical conservation. A study of the vernacular architecture of Pompeii. (4th March 2018) - Rajapaksha, Indrika; Fiorito, Francesco; Lazer, Estelle; Sartogo, Francesca
ABSTRACT: Investigations of the Vernacular Architecture of Pompeii revealed that little work had been carried out on the way the buildings respond to climate and to what extent these buildings were comfortable to the occupant given modern day standards. An integrated methodology from archaeology and architectural science techniques was developed and using a critical case study approach these questions were examined. A case study was selected as representative of the vernacular typology and that was suitably documented from the both methodological perspectives. A computer model was constructed from this data and simulations carried out using weather files from Naples. The findings from the computer simulation suggest that Romans would have been reasonably comfortable in summer; however, in winter the villas would need heating.